Treatment Exposure and Discontinuation in the PALbociclib CoLlaborative Adjuvant Study of Palbociclib With Adjuvant Endocrine Therapy for Hormone Receptor–Positive/Human Epidermal Growth Factor Receptor 2–Negative Early Breast Cancer (PALLAS/AFT-05/ABCSG-42/BIG-14-03). Issue 5 (10th February 2022) - Mayer, Erica L.; Fesl, Christian; Hlauschek, Dominik; Garcia-Estevez, Laura; Burstein, Harold J.; Zdenkowski, Nicholas; Wette, Viktor; Miller, Kathy D.; Balic, Marija; Mayer, Ingrid A.; Cameron, David; Winer, Eric P.; et al.
Abstract : PURPOSE: The PALLAS study investigated whether the addition of palbociclib, an oral CDK4/6 inhibitor, to adjuvant endocrine therapy (ET) improves invasive disease-free survival (iDFS) in early hormone receptor-positive (HR+), human epidermal growth factor receptor 2-negative (HER2–) breast cancer. In this analysis, we evaluated palbociclib exposure and discontinuation in PALLAS. METHODS: Patients with stage II-III HR+, HER2– disease were randomly assigned to 2 years of palbociclib with adjuvant ET versus ET alone. The primary objective was to compare iDFS between arms. Continuous monitoring of toxicity, dose modifications, and early discontinuation was performed. Association of baseline covariates with time to palbociclib reduction and discontinuation was analyzed with multivariable competing risk models. Landmark and inverse probability weighted per-protocol analyses were performed to assess the impact of drug persistence and exposure on iDFS. RESULTS: Of the 5, 743 patient analysis population (2, 840 initiating palbociclib), 1, 199 (42.2%) stopped palbociclib before 2 years, the majority (772, 27.2%) for adverse effects, most commonly neutropenia and fatigue. Discontinuation of ET did not differ between arms. Discontinuations for non–protocol-defined reasons were greater in the first 3 months of palbociclib, and in the first calendar year of accrual, and declined over time. No significant relationship was seen between longer palbociclib duration or ≥ 70% exposure intensity and improved iDFS. In the weighted per-protocol analysis, no improvement in iDFS was observed in patients receiving palbociclib versus not (hazard ratio 0.89; 95% CI, 0.72 to 1.11). CONCLUSION: Despite observed rates of discontinuation in PALLAS, analyses suggest that the lack of significant iDFS difference between arms was not directly related to inadequate palbociclib exposure. However, the discontinuation rate illustrates the challenge of introducing novel adjuvant treatments, and the need for interventions to improve persistence with oral cancer therapies. Abstract :